Empowerment of Children Based on Cultural Da’wah: A Study at Abu Bakar Ash-Shiddiq Foundation in Nagari Malai III Koto - Fauzi, Muhammad; Dewi, Arika Rahma; Arman, Lidya; Hadi, Rahmad Tri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study aims to analyze how cultural-based empowerment is carried out by the Abu Bakar Ash-Shiddiq Foundation, as well as the supportive and inhibiting factors in this empowerment process. The research methodology employed is qualitative with a phenomenological approach. Informants include foundation administrators, teachers, students (santri), and community leaders from Nagari Malai III Koto. Data were gathered through interviews, observations, and documentation. The study identified several key findings: first, the integration of cultural and religious values; second, a personalized approach in preaching; third, life skills development; fourth, strengthening social networks; fifth, continuous monitoring and evaluation; and sixth, psychosocial and emotional support. Implications include: strengthening family preaching programs, developing preaching skills, and enhancing the quality of family services.